Comparative immunohistochemical assessment of the effect of repetitive anesthesia with isoflurane and sevoflurane on rat liver - Ruxanda,Flavia (2016)
Abstract Background and objectives: Inhalation anesthetics are used in human, as well as veterinary medical practice. In the present study we investigated the effect of isoflurane and sevoflurane on rat hepatocytes. Methods: A total of 40 Wistar female rats were used in this study. Animals were divided in groups of 5 rats. Groups IM, SM served as control groups. Groups I1, I2, I3 were used to study isoflurane and S1, S2, S3 for sevoflurane study. They were anesthetized 3 times, for 2 h long, at 2 days interval with a concentration of: 1.5% isoflurane (I1, I2, I3) and 2% sevoflurane (S1, S2, S3). The oxygen supply throughout the anesthesia was 1 L O2/min. Groups IM, IS, I1, S1 were sacrificed immediately after the last anesthesia. Groups I2, S2 were sacrificed 6 h after the last anesthesia, and groups I3, S3, 24 h post-anesthesia. Liver samples were harvested to highlight caspase-3 in apoptotic hepatocytes. Results: Following isoflurane administration, there were less than 1% cells in apoptosis highlighted in rat livers from groups IM, I1 and I2. At 24 h post-anesthesia (group I3), a small number of apoptotic hepatocytes was highlighted (around 3.23% cells in apoptosis), with a strictly periacinar disposition, randomly distributed in a small number of hepatic lobules. After sevoflurane administration, less than 1% apoptotic hepatocytes were identified at all control moments throughout the study. Conclusions: The results suggest that the anesthetics do not present a considerable hepatotoxicity. The comparative assessment of the two anesthetics shows that sevoflurane is superior to isoflurane.